KONSENTRASI TIMBAL (Pb) DALAM AIR, SEDIMEN DAN Tubifex sp.PADA PERAIRAN YANG TERCEMAR LOGAM - Irawati Mei Widiastuti; Asus Maizar; Muhammad Musa; Diana Arfiati (Faculty of Science and Technology University Ibrahimy, 2018)
Lead is one of the heavy metals of pollutant sources that are highly toxic and can not be degraded thus accumulating in sediments and aquatic organisms including Tubifex worms. The objectives of the study were to determine the concentration and to analyze the correlation of lead concentration (Pb) contained in water, sediments and Tubifex worms. The research method used is survey. Samples were taken at the waters of the landfill. The determination of lead concentration (Pb) was used by Atomic Absorption Spectrophotometer (AAS) method. The results of measurements of lead concentration (Pb) in water, sediments and Tubifex worms tabulated in tables and graphs, were analyzed descriptively. To prove that the increase of Pb concentration in Tubifex worms along with the increase of Pb content in water and sediment, a simple linear regression analysis was performed. The results showed the concentration of Pb in water (0.4923 ± 0.0091 mg / L - 0.6647 ± 0.0067 mg / L), in sediments (1.3803 ± 0.0042 mg / L - 1.4530 ± 0 , 0046 mg / L) and in Tubifex worms (0.9213 ± 0.0032 mg / L - 0.9767 ± 0.0060 mg / L). The concentration of Pb in the Tubifex worm has increased with increasing concentrations of Pb in water and sediment.